Role of Hydraulic Signal and ABA in Decrease of Leaf Stomatal and Mesophyll Conductance in Soil Drought-Stressed Tomato - Li, Shuang; Liu, Junming; Liu, Hao; Qiu, Rangjian; Gao, Yang; Duan, Aiwang (Frontiers in Plant Science, 2021)
Stomatal conductance (gs) and mesophyll conductance (gm) represent major constraints to net photosynthetic rate (An) under drought, abscisic acid (ABA) plays a crucial role in gs response to drought. However, effects of endogenous ABA on gm under different soil water conditions remain unclear. In this study, the responses of gs and gm to ABA were investigated under progressive soil drying condition and their impacts on An and intrinsic water use efficiency (WUEi) were also elucidated in tomato grown in a climate-controlled greenhouse. gs and gm displayed different sensitivity to the decrease in soil water potential (Ψsoil). When Ψsoil ≥ -1.01 MPa, gs decreased as leaf water potential (Ψleaf) decreased, whereas ABA and gm did not significantly increase or decrease. During Ψsoil reduction from -1.01 to -1.44 MPa, as Ψleaf continued to decrease, both gs and gm decreased following with sustained significant accumulation of shoot sap ABA. Moreover, gs and gm limitation contributed to an almost 68-78% reduction in An under drought conditions. gm/gs increased as ABA accumulated, resulting in an increase of WUEi within Ψsoil range of -0.83 to -1.15 MPa. The present study provides further evidence that leaf hydraulic signal (Ψleaf) did not solely control of gs and gm at Ψsoil ≤ -1.01 MPa, the accumulation of ABA in shoot sap also maintained the decrease in gs and gm and thereby regulated An and WUEi.